Dinamika Struktur-Agensi dalam Perkembangan Industri Otomotif Indonesia - Adnan, Ricardi S. (UI Scholars Hub, 2014)
The focus of this paper is the dynamic relationship in automobile industry between entrepreneur and the power in 1969-1998. The length of this study can be divided in three periods: seeking the industrial form, going to maturity, and realizing the industrial autonomous. Looking back to the Old Order and analyzing along three periods, this research has found that the structure transformed the interactions between actors—“the shifting patronage”. Giddens approach and theory of “structuration” is really clear in this industry and the model of this phenomenon is called as “symbiotic relationship”. It is different from Chalmers (1996) analyzed through economical-politics analysis, or Aswicahyono (2009) explored the linkage of automobile industry regarding value chain theoretical framework, or Aswicahyono, Chatib Basri, and Hal Hill (2000) concluded the pattern of ownership and public policy regarding the political economy view. Through historical approach, data were collected by desk research, in-depth interview and several group discussions along 2008-2010 in Indonesia and Tokyo as well.